2016
DOI: 10.1016/j.ijnurstu.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Internet-based e-learning on clinician behaviour and patient outcomes: A systematic review

Abstract: This review found insufficient evidence regarding the effectiveness of e-learning on healthcare professional behaviour or patient outcomes, consequently further research in this area is warranted. Future randomised controlled trials should adhere to the CONSORT reporting guidelines in order to improve the quality of reporting, to allow evaluation of the effectiveness of e-learning programmes on healthcare professional behaviour and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
255
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(274 citation statements)
references
References 54 publications
(82 reference statements)
13
255
0
6
Order By: Relevance
“…Indeed, despite the progress that has been made in recent years, evaluating the effects of e-learning on real clinical behavior and client outcomes remains a challenge [60,65]. With regard to clinical behavior, researchers should assess the effect of new skills acquired via Web-based e-learning for brief MI on practice using methods other than those involving self-report measures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, despite the progress that has been made in recent years, evaluating the effects of e-learning on real clinical behavior and client outcomes remains a challenge [60,65]. With regard to clinical behavior, researchers should assess the effect of new skills acquired via Web-based e-learning for brief MI on practice using methods other than those involving self-report measures.…”
Section: Discussionmentioning
confidence: 99%
“…The consistent high fulfillment ratings in learning objectives, the low drop-out rates and the wide geographical catchment area suggest that E-learning programs with contemporary techniques are feasible and complementary pathways to improve pre-and post-graduate training in oncology. Further, the contemporary demands placed on the health workforce regarding a professional responsibility of maintaining the medical competence in practice, E-learning may play an important role in overcoming this challenge [32]. Finally, these hypothesis-generating data demonstrate that our educational paradigm has been well received across disciplines, professions and proficiency levels.…”
Section: Resultsmentioning
confidence: 83%
“…So far, there has been little experience in the evaluation of formative assessment within the widespread utilization of online learning in the education of medical specialists [14]. However, it has been shown that e-learning is at least as effective as traditional learning approaches, and superior to no instruction at all in improving health care professional behaviour [10]. …”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been various examples of the suitability of e-learning in medical education. The review by Sinclair et al [10] suggests that e-learning is at least as effective as traditional learning in improving health care professional behaviour. There are some examples of e-learning modules especially dedicated to the improvement of patient-physician communication skills [11-13].…”
Section: Introductionmentioning
confidence: 99%